Histología y morfometría de piel del pez Eremophilus mutisii(Trychomecteridae, Siluriformes) - Johanna Bonilla Lizarazo, Rocío (2008)
The tropical freshwater fish Eremophylus mutisii is endemic to the Cundinamarca highland in Colombia. Skin samples (0.5x0.5 cm2) were taken from 11 specimens at six body parts (mandible, dorsal head, dorsal trunk, caudal trunk, medial trunk and abdominal area), fixed in 4% formaldehyde, dehydrated in 95% ethanol and 99% isopropanol, embedded in paraffin and sectioned at 5 μm. The skin is made of two mayor cutaneous layers (epidermis and dermis) and a subcutaneous layer (hypodermis). The epidermis presents three layers with secre-tory cells, epithelial cells and a few taste buds; the dermis is separated from the epidermis by a basal membrane. We observed fibroblasts, two layers of melanophors and some blood vessels; the hypodermis has vascularized adipose tissue. Skin thickness changes with body area; the dermis is thicker than the epidermis; skin has more club cells than mucous cells. The medial trunk area has the largest number of club and mucous cells. The skin of E. mutissi seems to mainly have a protective function.